Evaluation of the Impact of Kosabangsa Activities in 2023 on Increasing Knowledge of Fish Processing from Fishermen of Serangai Village, Batik Nau District, North Bengkulu Regency - Parwito, Parwito; Edi Susilo; Indra Warman; Wismalinda Rita (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2024)
This study aims to evaluate the impact of the Kosabangsa 2023 program on improving the knowledge of fishermen's fish processing in Serangai Village, Batik Nau Sub-district, North Bengkulu Regency. Using both quantitative and qualitative approaches, we surveyed the group of fishermen who participated in the Kosabangsa 2023 program and conducted statistical data analysis to assess its impact on the knowledge, skills, and practices of processing fishermen's catch for income generation. The survey results showed that most respondents reported an increase in knowledge of fish processing, packaging and marketing after participating in the kosabangsa program. In addition, there was a significant increase in fish processing productivity due to the adoption of new technologies provided in the kosabangsa program for the communities participating in the program. However, challenges such as frequent power outages made the implementation of the program less successful. These findings suggest that the kosabangsa program is effective in improving the quality of human resources in processing captured fish, and that there is a need to increase the sustainability of the program to achieve more optimal results.